OS EFEITOS DA POLÍTICA DE FOCALIZAÇÃO NO ENSINO FUNDAMENTAL (FUNDEF) NO FINANCIAMENTO DO ENSINO MÉDIO NO ESTADO DO MARANHÃO NO PERÍODO DE 1996-2006 - S. Alves (IESMA / UEMA / UFPA), Ms. Antonio (2012)
The text analyzes the Fundef in Maranhão and its effects on High School spending in that State in theperiod of 1996-2006 with a view to discuss the effectiveness of this funding policy that focused onlyon one stage of the basic education. For this, discu1990s, with an emphasis on education funding from Fundef and analyzes the dynamic budgetrevenues of Education Function; participation / contribution of the revenues of Fundef in totalrevenue of Education, resulting the collaboration of the Union for a poor financially state. Thesedata were collected and systematized from General Balance of the State of Maranhão and refer tothe period from 1996 to 2006. It concludes that the conditions that were offeredthe State in the period under analysisteaching.